2019
DOI: 10.3390/cancers12010108
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Arsenic Trioxide in Ameliorating ABT-737 Target Therapy on Uterine Cervical Cancer Cells through Unique Pathways in Cell Death

Abstract: ABT-737, a B cell lymphoma-2 (Bcl-2) family inhibitor, activates apoptosis in cancer cells. Arsenic trioxide is an apoptosis activator that impairs cancer cell survival. The aim of this study was to evaluate the effect of a combination treatment with ABT-737 and arsenic trioxide on uterine cervical cancer cells. MTT (3-(4,5-dimethylthiazol-2-yl)-25-diphenyltetrazolium bromide) assay revealed that ABT-737 and arsenic trioxide induced a synergistic effect on uterine cervical cancer cells. Arsenic trioxide enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…The fixed cells were stained with propidium iodine, and cell cycle distribution was analyzed by flow cytometry. The complete protocol for both analyses has been described elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fixed cells were stained with propidium iodine, and cell cycle distribution was analyzed by flow cytometry. The complete protocol for both analyses has been described elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The HeLa cells (7 × 10 4 cells/well) and SiHa cells (7 × 10 4 cells/well) were seeded in a 24‐well plate with 100 μl of the culture medium. The medium was removed after 24 h of culturing, and 100 μl of a medium containing 0.5 mg/ml MTT was applied 26 …”
Section: Methodsmentioning
confidence: 99%
“…The proposed mechanism is that arsenic trioxide reduces anti-apoptotic protein Mcl-1 in Caski cells and enhancement of ABT-737-induced apoptosis and caspase-7 activation. 74 These suggested that ABT-737 and related BH3 mimetic drugs, in combination or alone, may be of value as a new therapeutic option for dedifferentiated thyroid carcinomas. ABT-737 also appears to work through triggering platelet phosphatidylserine in a caspase-dependent manner.…”
Section: New Therapeutic Agents and Novel Drug Targetmentioning
confidence: 99%